2001
DOI: 10.1016/s0735-1097(01)01364-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening patients with chest pain in the emergency department using electron beam tomography: a follow-up study

Abstract: These data support previous reports demonstrating that the presence of CAC in a symptomatic cohort is a strong predictor of future cardiac events. This study supports the use of EBT in a symptomatic cohort with prompt discharge of those patients with negative scans. Furthermore, the absence of CAC is associated with a very low risk of future cardiac risk events in this population over the subsequent seven years (annual event rate <1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(125 citation statements)
references
References 15 publications
6
116
0
2
Order By: Relevance
“…Coronary calcium scores > the 75 th percentile for age and gender can also be used to identify individuals with an elevated atherosclerotic plaque burden and increased higher ASCVD risk 75 . 0…”
Section: Advanced Subclinical Coronary Atherosclerosis Burdenmentioning
confidence: 99%
“…Coronary calcium scores > the 75 th percentile for age and gender can also be used to identify individuals with an elevated atherosclerotic plaque burden and increased higher ASCVD risk 75 . 0…”
Section: Advanced Subclinical Coronary Atherosclerosis Burdenmentioning
confidence: 99%
“…7 Coronary artery calcium (CAC) correlates directly with coronary atherosclerosis and is a marker of plaque burden. [8][9][10][11] Quantification of CAC with cardiac computed tomography (CT) is sensitive, accurate, and reproducible. [10][11][12] Positive findings for CAC on cardiac CT are nearly 100% specific for atheromatous plaque.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Positive findings for CAC on cardiac CT are nearly 100% specific for atheromatous plaque.…”
Section: Mayo Clinmentioning
confidence: 99%
“…In a study of 568 low-risk ED patients with chest pain, those with negative coronary CTA did not have any adverse outcomes (nonfatal AMI or death) within 30 days of the index ED visit [25]. Prior studies have shown that coronary CTA has high diagnostic accuracy (82-100% sensitivity, 82-98% specificity, negative predictive value of 95-100%) in low-risk patients for detection of coronary artery disease [26][27][28][29][30][31][32][33][34]. Coronary CTA has been shown to be as safe [17] and more cost effective [18] than other methods of evaluating these patients.…”
Section: Discussionmentioning
confidence: 99%